18F-NaF PET/CT Imaging of Brain Metastases. (July 2016) - Salgarello, Matteo; Lunardi, Gianluigi; Inno, Alessandro; Pasetto, Stefano; Severi, Fabrizia; Gorgoni, Giancarlo; Gori, Stefania
Abstract : Abstract: 18 F-NaF is a radiopharmaceutical widely used in PET imaging to detect bone metastases. Several cases of 18 F-NaF uptake from brain metastases have been described, but a specific protocol for the evaluation of brain metastases with 18 F-NaF has not been developed yet. Here we report images of 18 F-NaF PET/CT, standard CT, and MRI of a brain metastasis in a patient with non–small lung cancer. Through a dynamic acquisition procedure, we have identified the first minutes after injection as the preferable time point of imaging acquisition for the study of brain metastases with 18 F-NaF.